If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -1b = 3b + 30 Reorder the terms: 12 + -1b = 30 + 3b Solving 12 + -1b = 30 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 12 + -1b + -3b = 30 + 3b + -3b Combine like terms: -1b + -3b = -4b 12 + -4b = 30 + 3b + -3b Combine like terms: 3b + -3b = 0 12 + -4b = 30 + 0 12 + -4b = 30 Add '-12' to each side of the equation. 12 + -12 + -4b = 30 + -12 Combine like terms: 12 + -12 = 0 0 + -4b = 30 + -12 -4b = 30 + -12 Combine like terms: 30 + -12 = 18 -4b = 18 Divide each side by '-4'. b = -4.5 Simplifying b = -4.5
| 13x+10=3(3x+6)+4x-8 | | -8-23=159 | | y=(a^2)+4a+8 | | 5x+39=7x+1 | | -40=8+8 | | 9x^2-144=576 | | (2x/5)+6=(x/5) | | 3.4-3x=1.4+x | | -2=(d-5)/6 | | 10y-20=-4y | | y=5(1/2)+7 | | 99=105-1.02x | | 19(-9-4m)=42 | | 3/5k-(k+1/3)=1/15(k+1) | | 4+2x-2=8x+2-4x | | 99=207-0.85*120-1.02x | | 45000x=5 | | -3=5(1/2)+7 | | 6.4/x=2/3 | | -3+=-17 | | -4=-(d+7)/3 | | 45000/x=5 | | m-26=47 | | (13b-2)-4(3b+4)=-5 | | -4=-d+7/3 | | y=(5x^3)-(3x^2)-2x | | 5v-10=55 | | 9x=5-7 | | -x/2=(-28) | | 5x/3-x=x/15-12/5 | | (13s+8)(5s-15)=0 | | 3a^2b+2a^2b^2= |